The judgment of God and the rise of ‘Inclusivism’ in contemporary American evangelicalism - Kuligin, Victor (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DTh (Systematic Theology and Ecclesiology))--University of Stellenbosch, 2008.